Maybe We Don't Need To Learn to Code. - MANJOO, FARHAD (New York Times, 2023)
The article explores the transformation of computer programming into a widely accessible skill across various fields through the rise of artificial intelligence, exemplified by tools like OpenAI Codex and Google's AlphaCode.